Down-regulation of types I, II and III inositol 1,4,5-trisphosphate receptors is mediated by the ubiquitin/proteasome pathway. - Oberdorf, J (1999)
Activation of certain phosphoinositidase-C-linked cell-surface receptors is known to cause an acceleration of the proteolysis of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] receptors and, thus, lead to Ins(1,4,5)P3-receptor down-regulation. In the current study we have sought to determine whether the ubiquitin/proteasome pathway is involved in this adaptive response. The data presented show (i) that activation of phosphoinositidase-C-linked receptors causes Ins(1,4,5)P3-receptor ubiquitination in a range of cell types (AR4-2J cells, INS-1 cells and rat cerebellar granule cells), (ii) that the Ins(1,4,5)P3-receptor down-regulation induced by activation of these receptors is blocked by proteasome inhibitors, (iii) that all known Ins(1,4,5)P3 receptors (types I, II and III) are substrates for ubiquitination, (iv) that ubiquitination occurs while Ins(1,4,5)P3 receptors are membrane-bound, (v) that Ins(1,4, 5)P3-receptor ubiquitination and down-regulation are stimulated only by those agonists that elevate Ins(1,4,5)P3 concentration persistently, and (vi) that a portion of cellular Ins(1,4,5)P3 receptors (those that are not type-I-receptor-associated) can be resistant to ubiquitination and degradation. In total these data indicate that the ubiquitin/proteasome pathway mediates Ins(1,4, 5)P3-receptor down-regulation and suggest that ubiquitination is stimulated by the binding of Ins(1,4,5)P3 to its receptor.